The Minimeter - Enabling communication technology for people with severe brain injuries. - Breidegard, Björn (Technology & Disability, 2013)
BACKGROUND: The Minimeter is a communication tool developed for people with severe brain injuries (almost no mobility, limited gaze control and eye blink ability, without speech, and with varying degrees of cognitive difficulties). Previously, they have not been able to communicate reliably even on a yes- or no-level. OBJECTIVE: To capture even minor movements intended for interaction and communication (starting at a yes-no level) with the environment or people around and to yield immediate and intuitive feedback to the users to help them develop both their abilities and ambitions. METHODS: Longitudinal iterative design of the appropriate communication technology in close collaboration with the intended users in their situated everyday life. RESULTS: During more than 13 years about 30 people with severe brain injuries have achieved new communication abilities through The Minimeter. The tool and its manual, utilizing the parallel advancements in overall computer and game technology, are now freely available as specially designed software for a standard PC with a web camera or accelerometer. CONCLUSIONS: The Minimeter opens up for learning and hope and provides earlier inaccessible possibilities for users with severe cognitive and mobile limitations to express and realize their needs, wishes and sometimes even dreams.